Mathematical proficiency siswa pada materi persamaan garis lurus ditinjau dari resiliensi matematis - Zandy, Satila Sufita; Negara, Habibi Ratu Perwira (Mahesa Research Center, 2024)
This research explains students' mathematical proficiency by considering mathematical resilience in solving problems. This research sample involved 30 grade 8 junior high school students in Pringgarata, who were chosen randomly. The research method used is descriptive qualitative. Data was collected through a mathematical resilience questionnaire with 12 statements, as well as a mathematical proficiency test consisting of 2 essay questions and an interview guide. The research results show that students with high mathematical resilience have good mathematical proficiency, and students in this category have a good understanding of concepts, where conceptual fluency in solving problems, choosing strategies, and adaptive reasoning are used appropriately. Students have a productive disposition, which can be seen in their being confident in their answers in solving each question. Meanwhile, moderate mathematical resilience has good mathematical proficiency, and students in this category have a good understanding of concepts, strategies, and adaptive reasoning. However, when students' conceptual fluency is in the medium category, failure to solve the problem results in a less productive disposition, productive disposition refers to self-confidence. However, students with low mathematical resilience have good mathematical proficiency, and students in this category have a good understanding of concepts and strategies. During adaptive reasoning and conceptual fluency, students in the low category failed to solve the problem, which resulted in a less productive disposition.